2020
DOI: 10.3390/en13113016
|View full text |Cite
|
Sign up to set email alerts
|

A Chronological Literature Review of Electric Vehicle Interactions with Power Distribution Systems

Abstract: In the last decade, the deployment of electric vehicles (EVs) has been largely promoted. This development has increased challenges in the power systems in the context of planning and operation due to the massive amount of recharge needed for EVs. Furthermore, EVs may also offer new opportunities and can be used to support the grid to provide auxiliary services. In this regard, and considering the research around EVs and power grids, this paper presents a chronological background review of EVs and their interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…In order to solve this dilemma, the government has invested a lot of energy in infrastructure deployment. Service operation of electric vehicle charging stations has become a hot issue for scholars; for example, the deployment of charging stations [7][8][9], electric vehicle interaction with power systems [10][11][12] and the VRP problem with charging stations [13][14][15][16][17][18]. However, as the main mode of energy supply for electric vehicles, charging mode also has two main problems that restrict the industrialization of electric vehicles.…”
Section: Current Bottleneck In Charging Modementioning
confidence: 99%
“…In order to solve this dilemma, the government has invested a lot of energy in infrastructure deployment. Service operation of electric vehicle charging stations has become a hot issue for scholars; for example, the deployment of charging stations [7][8][9], electric vehicle interaction with power systems [10][11][12] and the VRP problem with charging stations [13][14][15][16][17][18]. However, as the main mode of energy supply for electric vehicles, charging mode also has two main problems that restrict the industrialization of electric vehicles.…”
Section: Current Bottleneck In Charging Modementioning
confidence: 99%
“…Previous studies in this field have been carried out for distribution networks over different locations in the world and in Sweden. Within the extensive review carried out in Reference [9], demand side management and scenario-based analyses were been identified as categories with a major presence in the literature. In the study carried out in Reference [10], charging behavior factors were shown to have a strong influence on the results.…”
Section: Related Workmentioning
confidence: 99%
“…This study also examined various EV load modeling techniques to deal with uncertainties. In [17], the authors categorized EV-related studies based on the time of publication and the impact of EVs on the distribution network. In [18], the capabilities and challenges of EVs to support network, residential, and business buildings are examined, and, accordingly, EV services are divided into three categories, including V2G, V2H, and V2B.…”
Section: Introductionmentioning
confidence: 99%